Presence of Accessible Equipment and Interior Elements in Primary Care Offices - Nancy R. Mudrick; LeeAnn C. Swager; Mary Lou Breslin (Mary Ann Liebert, 2019)
Purpose: To describe the disability accessibility level of primary care office interiors and the presence of accessible examination equipment. Methods: Data from on-site audits of 3993 primary care offices in California for 2013?2016 are descriptively analyzed. Architectural access is assessed using an instrument based on ADA Accessibility guidelines (ADAAG), along with noting accessibility of examination equipment. Results: Compliance across architectural elements was ?85%. Accessible examination tables and scales were observed in 19.1% and 10.9% of offices, respectively. Conclusions: Proactive accessibility auditing makes visible the infrequent presence of accessible examination equipment. It offers data for tracking progress to increase medical office disability access.